Do Fiscal and Monetary Policies Cooperate or Conflict with Each Other in Nigerian Economy? - Harrison Ogbeide Eromosele; David Umoru (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
The determination for this study was to ascertain if fiscal and monetary policies are cooperating or rather conflicting with each other in Nigerian economy. Government disbursement and growth of money stock were used to denote fiscal and monetary policy variables. Two reduced form equations of monetary and fiscal policies were specified from underlying structural model. This yielded fourteen RF parameters in contrast to eleven structural parameters and so we had system of over-identification. These prompted use of IV estimators such as GMM and 3SLS. Estimates show similar findings for both estimators as we found evidence that fiscal policy does not respond favourably to monetary policy as monetary policy was found to have an insignificant effect on the fiscal policy. More so, fiscal policy does not respond to lag effect of monetary policy. Relatively, monetary policy responds favourably to fiscal policy. The lag effect of money supply was also found to have a significant impact on money supply. Empirical finding so upholds that Nigerian economy is fiscally overriding notwithstanding money being an integral part of all macroeconomic variables. Significance of lag effects of both fiscal and monetary policy is reflection that implementation process of both policies is excessively time overshadowing. Consequently, there is need for building well-organized units of fiscal and monetary authorities that can accelerate implementation process of these policies.